The Effect of Public-Private Partnership on Service Quality – A Field Study on School Transportation in Al-Makhwah Governorate Saudi Arabia – - Al-Muawi, Abdullah bin Saeed; Taibah, Hassan bin Abdul Qadir; Jafri, Ali bin Omar (Journal of Economic, Administrative and Legal Sciences, 2021)
This research aimed to assess the impact of raising service quality levels that are provided through public and private partnerships. The researchers will analyze the educational transportation in Al-Makhwah Governorate, Al-Baha region. An empirical investigation was performed to illustrate the impact of the partnership on the quality of educational transportation. The researchers targeted the beneficiaries of middle school students to one department of education in the governorate. The number of participating students reached (338) students. The results show there was a statistically significant difference between the quality of public-private partnership buses and the quality of private buses. As such, the quality of services was higher in public-private partnership buses than in buses owned by private companies working by themselves. In addition, a significant improvement in the satisfaction in dex for service recipients after partnering with the private sector, in addition to an improvement in security and safety measures. Therefore, public sector engagement with the private sector provides the possibility for continuous development of services while maintaining current performance indicators.
Keywords: partnership between the public and private sectors; quality of services; school transportation; Al-Makhwah Governorate; Saudi Arabia